2021
DOI: 10.3390/ijms22158115
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of microRNA and Intracerebral Hemorrhage: Roles in Neuroinflammation

Abstract: Intracerebral hemorrhage (ICH) is a major public health problem and devastating subtype of stroke with high morbidity and mortality. Notably, there is no effective treatment for ICH. Neuroinflammation, a pathological hallmark of ICH, contributes to both brain injury and repair and hence, it is regarded as a potential target for therapeutic intervention. Recent studies document that microRNAs, small non-coding RNA molecules, can regulate inflammatory brain response after ICH and are viable molecular targets to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 187 publications
0
5
0
Order By: Relevance
“…ICH stands out among stroke, for the severe pathological results it routinely produces. Increasing evidence suggested that apoptosis [38,39], neuroinflammation [40][41][42][43], immunity [44], and the BBB [45] play an important role in ICH. Therefore, although many intervention measures for ICH and its sequelae have been studied (e.g., hemostatic therapy, blood pressure control, hematoma evacuation, and various nerve protection strategies), clinical benefits are still elusive.…”
Section: Discussionmentioning
confidence: 99%
“…ICH stands out among stroke, for the severe pathological results it routinely produces. Increasing evidence suggested that apoptosis [38,39], neuroinflammation [40][41][42][43], immunity [44], and the BBB [45] play an important role in ICH. Therefore, although many intervention measures for ICH and its sequelae have been studied (e.g., hemostatic therapy, blood pressure control, hematoma evacuation, and various nerve protection strategies), clinical benefits are still elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inflammatory responses may also affect hematoma expansion via breaking the balance of coagulation. Neuroinflammation induced by ICH is characterized by increased activation of microglia/monocyte-derived macrophages and the subsequent release of proinflammatory and anti-inflammatory mediators 34 . Neutrophils are the earliest leukocytes recruited from peripheral blood into the brain 35 .…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNA, miR) are small conserved non-coding single-stranded RNA. They can regulate inflammatory response after ICH and are viable molecular targets to alter brain function (124,125). Over the past few years, there has been a surge of research addressing the role of various miRs in the pathophysiology of ICH (126).…”
Section: Potential Microrna Therapymentioning
confidence: 99%